2016
DOI: 10.1007/s12192-016-0728-y
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolides and bilobalide protect BV2 microglia cells against OGD/reoxygenation injury by inhibiting TLR2/4 signaling pathways

Abstract: Ginkgolide and bilobalide are major trilactone constituent of Ginkgo biloba leaves and have been shown to exert powerful neuroprotective properties. The aims of this study were to observe the inhibitory effects of ginkgolide and bilobalide on the activation of microglial cells induced by oxygen-glucose deprivation and reoxygenation (OGD/R) and the specific mechanisms by which these effects are mediated. For detecting whether ginkgolide and bilobalide increased cell viability in a dose-dependent manner, BV2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 92 publications
5
40
0
Order By: Relevance
“…These results are consistent with the attenuation of oxidative damage by CBD in a diabetic retinopathy model [24], in PC12 cells stimulated with β-amyloid [9], and in oligodendrocyte progenitor cells treated with H 2 O 2 [8], and with the antioxidant property of CBD in rats with renal ischemia/reperfusion injury [25]. Furthermore, consistent with previous studies [26], [27], [28], we found that OGD/R insult markedly reduced cell viability and induced apoptosis and PARP-dependent cell death, which were significantly attenuated by the administration of CBD.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with the attenuation of oxidative damage by CBD in a diabetic retinopathy model [24], in PC12 cells stimulated with β-amyloid [9], and in oligodendrocyte progenitor cells treated with H 2 O 2 [8], and with the antioxidant property of CBD in rats with renal ischemia/reperfusion injury [25]. Furthermore, consistent with previous studies [26], [27], [28], we found that OGD/R insult markedly reduced cell viability and induced apoptosis and PARP-dependent cell death, which were significantly attenuated by the administration of CBD.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies have shown that MG produce TNFα, IL6 and IL1β in response to OGD exposure (Chock and Giffard, 2005; Zhou et al, 2016); this was also confirmed in our study. The levels of TNFα, IL6 and IL1β produced by BV2 and MG were increased by OGD ( P < 0.001, Figures 2A,B).…”
Section: Resultssupporting
confidence: 91%
“…In addition, BB also acts on astrocytes to alleviate the swollen of brain (Goldie & Dolan, ). Our result that BB reduced OGD‐R‐induced apoptosis is also consistent with reports showing that BB attenuated the OGD‐induced apoptosis by reversing cleaved caspase‐3, Bax/Bcl‐2, and cleaved PARP‐1 in microglia cells (Zhou et al, ). BB also reduced apoptosis in α‐Synuclein treated SH‐SY5Y cell (Hua et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Bilobalide (BB) is a sesquiterpene trilactone constituent that accounts for~2.9% of the standardized Ginkgo biloba extract EGb 761, which has been widely used to treat a variety of neurological disorders including cerebral ischemia and neurodegeneration (Attia et al, 2012;Deng, Wei, & Zhang, 2006;Oskouei et al, 2013;Sadowska-Krepa et al, 2017;Vellas et al, 2012;Yancheva et al, 2009). Substantial experiments indicate that BB is a neuroprotective agent with multiple mechanisms of action (Goldie & Dolan, 2013;Jiang et al, 2014;Lang et al, 2011;Mdzinarishvili, Kiewert, Kumar, Hillert, & Klein, 2007;Suzuki, Sato, Takezawa, Usuki, & Okada, 2011;Zhou et al, 2016). However, its effects on astrocytes remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%